Pringle maneuver increases the risk of anastomotic leakage after colonic resection in rats. Issue 5 (May 2018) - Jansen-Winkeln, Boris; Tagkalos, Evangelos; Heimann, Axel; Gaiser, Timo; Hirsch, Daniela; Gockel, Ines; Mittler, Jens; Lang, Hauke; Heinrich, Stefan
Abstract: Background: Many centers use the Pringle's maneuver during liver resections. Since this maneuver might impair healing of bowel anastomoses, we evaluated its influence on the healing of colonic anastomosis in rats. Methods: Male Wistar rats underwent median laparotomy and sigmoid resection with end-to-end anastomosis under inhalation anesthesia. Thereafter, rats received a 25 minutes Pringle's maneuver (PM, group 1) or were kept under anesthesia for the same period of time (group 2). The anastomotic bursting pressure (BP) was measured on postoperative days (POD) 3, 6 and 9. Hematoxylin and Eosin (H&E) staining was used for histopathological evaluation of the anastomosis. The Mann-Whitney U and χ 2 -tests were used, p<0.05 values were considered significant. Results: All animals (n=48) lost body weight (BW) until POD3 (95.2% vs. 85.7%, p=0.003), and BW remained lower after PM (106.2% vs. 92.8%, p=0.001). The anastomotic BP was lower in group 1 compared to group 2 on POD 3 (116mmHg vs. 176.28mmHg, p=0.001), POD 6 (182.8mmHg vs. 213mmHg, p=0.029) and POD 9 (197.2mmHg vs. 251.7mmHg, p=0.009), and mortality was higher in group 1 (1 vs. 7, p=0.022). Conclusions: Pringle's maneuver increases anastomotic complications in rats. Therefore, a Pringle's maneuver should be avoided during simultaneous liver and colorectal surgery.